Feasibility and acceptability of a culturally adapted psychological first aid training intervention (Preparing Me) to support the mental health and well-being of front-line healthcare workers in China: a feasibility randomized controlled trial - Ling Wang; Ian Norman; Tao Xiao; Yamin Li; Xizhao Li; Ting Liu; Jianjian Wang; Lina Zeng; Ziqing Zhong; Chengzhu Jian; Mary Leamy (European Journal of Psychotraumatology, 2024)
ABSTRACTBackground: Psychological first aid (PFA) training helps to prepare healthcare workers (HCWs) to manage trauma and stress during healthcare emergencies, yet evidence regarding its effectiveness and implementation is lacking.Method: A two-arm feasibility randomized controlled trial design was conducted in a Chinese tertiary hospital. Participants were randomly allocated to receive either a culturally adapted PFA training (the intervention arm) or psychoeducation (the control arm). Feasibility indicators and selected outcomes were collected.Results: In total, 215 workers who expressed an interest in participating in the trial were screened for eligibility, resulting in 96 eligible participants being randomly allocated to the intervention arm (n = 48) and control arm (n = 48). There was a higher retention rate for the face-to-face PFA training session than for the four online group PFA sessions. Participants rated the PFA training as very helpful (86%), with a satisfaction rate of 74.25%, and 47% reported being able to apply their PFA skills in responding to public health emergencies or providing front-line clinical care. Positive outcome changes were observed in PFA knowledge, skills, attitudes, resilience, self-efficacy, compassion satisfaction, and post-traumatic growth. Their scores on depression, anxiety, stress, and burnout measures all declined. Most of these changes were sustained over 3 months (p < .05). Repeated measures analysis of variance found statistically significant interaction effects on depression (F2,232 = 2.874, p = .046, [Formula: see text] = .031) and burnout (F2,211 = 3.729, p = .018, [Formula: see text] = .037), indicating a greater reduction in symptoms of depression and burnout with PFA compared to psychoeducation training.Conclusion: This culturally adapted PFA training intervention was highly acceptable among Chinese HCWs and was feasible in a front-line care setting. Preliminary findings indicated positive changes for the PFA training intervention on knowledge, skills, attitudes, resilience, self-efficacy, compassion satisfaction, and post-traumatic growth, especially a reduction of depression and burnout. Further modifications are recommended and a fully powered evaluation of PFA training is warranted.